Distingsi Prosedural dan Nilai Filosofis Shalat Sunnah: Analisis Integratif Kaifiyah Shalat Gerhana, ID, Istisqa, dan Tasbih di Era Modern - Alya Tsaabitah; Nur Wakhid; Fanny Oktavia Anggraeni; Mochammad Rafli Hidayat; Sania Mutia Salsabila (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Sunnah prayers play a significant role in the spiritual aspect of Muslims as a means of drawing closer to Allah SWT. This study aims to explore the kaifiyah of sunnah prayers, which include the eclipse prayer, Eid prayer, istisqa prayer, and tasbih prayer, and their relevance to the lives of Muslims in the contemporary era. The approach used in this study is library research with a descriptive-qualitative method through analysis of fiqh literature, hadith, and the latest scientific journals. The research findings show that each sunnah prayer has unique procedures, requirements, and meanings that focus on strengthening spiritual, social, and moral values ​​for Muslims. The eclipse prayer teaches a lesson about the awareness of the greatness of Allah, Eid prayer strengthens Islamic brotherhood, istisqa prayer instills a sense of human dependence on Allah when facing environmental issues, while tasbih prayer serves as a means of purifying the soul through dhikr and forgiveness of sins. The implementation of sunnah prayers in the lives of Muslims today shows that worship is not merely ritualistic, but also has broad social and spiritual impacts.